Pelatihan Strategi Penulisan Artikel Ilmiah pada Jurnal Bereputasi Nasional dan Internasional bagi Guru di SMKN 1 Sekotong Kabupaten Lombok Barat - Taufik Suadiyatno; Dedi Sumarsono; Muliani Muliani; Moh. Arsyad Arrafii; Abdul Kadir Bagis (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2020)
This community service program aimed to improve teachers’ anthusiastic in SMKN 1 Sekotong, West Lombok to conduct articles to be published in national accredited and international journal. The method used in this program divided into three stages such as 1) early stage includes koordination between the program team with the principle of SMKN 1 Sekotong; 2) implementation stage includes scientific article training; and 3) evaluation stage that used as the overview of the next program. The materials in this program was presented mostly in term of describing the technique of writing good articles therefore they deserve to be published in national accredited or international journal. This community service program was conducted in SMKN 1 Sekotong which was followed by the pcinciple and 23 teachers. The conclusion of this program was there was an improvement of teachers’ anthusiastic to publish their scientific articles in national accredited and international journal.